2019
DOI: 10.1111/1750-3841.14684
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Physicochemical Characteristics of Garlic Produced from South Korea and China

Abstract: Garlic is widely cultivated and frequently used as a spice in South Korea, due to its characteristic flavor. It is rich in sulfur‐containing compounds (for example, allicin) and nonsulfur elements (for example, phosphorus and potassium). During the last few years, the cultivation area of garlic in South Korea has gradually decreased, one of the reasons being the increase in low‐priced imported garlic from China. Several studies have reported the discrimination of foods originating from different geographical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…These values are typical for FG originating from the Czech Republic, where the moisture content is usually between 55 and 70% [12]. When compared with garlic from other countries, samples originating from South Korea have an average moisture content of 63.43%, whereas Chinese samples have 66.76% [21]. Moreover, Shin et al [22] reported that Chinese garlic samples had a moisture content higher than 70% on average.…”
Section: Resultsmentioning
confidence: 93%
“…These values are typical for FG originating from the Czech Republic, where the moisture content is usually between 55 and 70% [12]. When compared with garlic from other countries, samples originating from South Korea have an average moisture content of 63.43%, whereas Chinese samples have 66.76% [21]. Moreover, Shin et al [22] reported that Chinese garlic samples had a moisture content higher than 70% on average.…”
Section: Resultsmentioning
confidence: 93%
“…In addition to distinguishing garlic from different sources morphologically and physiologically, there have been some previous reports proposing other identification methods. For example, (1) isozyme analysis methods; 11 (2) isotope ratio mass spectrometry (IRMS); 7,12 (3) methods to link genotypes to agronomic traits using DArTseq; 13 (4) the multi-element distribution of garlic from different origins has been compared using various spectrometric techniques such as inductively coupled plasma emission spectrometry (ICP-OES), inductively coupled plasma mass spectrometry (ICP-MS), and inductively coupled plasma atomic emission spectroscopy (ICP-AES); 14–19 (5) other determination methods rely on metabolomics, including amino acids and their derivatives, organic sulfides, volatile organic compounds (VOCs), characteristic markers, and metabolomics fingerprints. 8,14,20–22 The identification of adulteration in food products is crucial for ensuring consumer safety and maintaining the integrity of the market.…”
Section: Introductionmentioning
confidence: 99%